Coordination, Organizations, Institutions, Norms, and Ethics for Governance of Multi-Agent Systems XVI 27th International Workshop, COINE 2023, London, UK, May 29, 2023, Revised Selected Papers - Fornara, Nicoletta; Cheriyan, Jithin; Mertzani, Asimina (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 27th International Workshop on Coordination, Organizations, Institutions, Norms, and Ethics for Governance of Multi-Agent Systems, COINE 2023, held in London, UK, on May 29, 2023 (co-located with 22nd International Conference on Autonomous Agents and Multi-Agent Systems (AAMAS)). This book contains 10 full papers which are the extended and revised versions of the papers accepted to the workshop. The papers were carefully reviewed and selected from 13 submissions. They are organized in topical sections as follows: Norms, Social contracts, Institutions, and Privacy; Studies on the notion of Value; and Argumentation and Conventions.
Norms, Social contracts, Institutions, and Privacy -- PACCART: Reinforcing Trust in Multiuser Privacy Agreement Systems -- Generalising Axelrod's Metanorms Game through the use of explicit domain-specific norms -- Incentivising Participation With Exclusionary Sanctions -- Governing Agents on the Web (Blue Sky Ideas) -- Studies on the notion of Value -- Arguments for Framing the Value Alignment Problems with Online Institutions -- Adding Preferences and Moral Values in an Agent-Based Simulation framework for High-Performance -- Computing -- Social Value Orientation and Integral Emotions in Multi-Agent Systems -- Argumentation and Conventions -- Towards Ethical Argumentative Persuasive Chatbots -- Uncertain Machine Ethical Decisions Using Hypothetical Retrospection -- Towards Convention-Based Game Strategies.
Keywords: Artificial intelligence; Computers, Special purpose; Computer science; Coding theory; Information theory; Artificial Intelligence; Special Purpose and Application-Based Systems; Theory of Computation; Coding and Information Theory